Aposentadoria Especial: atividade periculosa no Regime Geral de Previdência Social - Mattes, Lúcio Cazzuni (2017)
The present dissertation aims at the special retirement approach under the periculosa approach with the General Regime of Social Security, accomplished through the analysis of the structure rule of § 1 of article 201 of the Federal Constitution that allows the adoption of requirements And differentiated criteria when exercising under special conditions that damage health or physical integrity. In the attempt to sediment the object brought to study, the interpreter traces a parallel between the social security right and the labor law, through the analysis of Law no. 8,133 / 91, especially articles 57 and 58 for the Consolidation of Labor Laws, Decree-Law no. 5,452 / 43, and the Regulatory Norms issued by the Ministry of Labor. On the other hand, it enters into the structure of the legal-social-security norm, setting forth the compositional elements of the antecedent and consequent normative, necessary to the solidification of the scientificity that the study demands, before the application of a general theoretical character in any area of legal knowledge. It crosses the disparate compositional elements of the legal system in the normative triad, setting the condition of possibility of the periculosa activity to translate the legal-social norm of the special retirement with sustentation in the elements, principles and of the rules, which would assure the application of the norm of structure Based constitutionally with art. 193: the social security securi- ty and, consequently, the welfare security